LEARNING NOT TO SPEAK IN TONGUES: THOUGHTS ON THE LIBRARIAN OF BASRA - Jardine, David; Naqvi, Rahat (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
We explore the nature of knowledge and education and how Islamic traditions have shaped understanding of these matters. We contrast this with contemporary images of “Taliban‐like” schools full of rote repetition and harsh, authoritarian literalism. Some of the history of Islamic scholarship venerates a much more generous relationship to knowing. We link these explorations to a recently published children’s picture book, a true story about a librarian in Basra, Iraq, during the recent American invasion. Even if it is a “true story,” we consider what its truth is and whether educators, might or should or could stand by this truth. Key words: Islamic philosophy, curriculum knowledge, knowledge formation, politics and education, multiculturalism Nous explorons ici la nature du savoir et de lʹéducation et comment la tradition islamique a modelé leur compréhension. Nous comparons les images contemporaines des écoles ʺstyle Talibanʺ qui sont faites de ʺpar coeurʺ et de litéralité dure et autoritaire avec certaines écoles dans lʹhistoire de lʹIslam qui affichent une plus grande générosité face au savoir. Nous établissons un lien entre ces notions et un livre illustré pour enfants récemment publié, une histoire vécue dʹun libraire de Basra, en Iraq, pendant la récente invasion américaine. Même si cette histoire est une ʺhistoire vraie ʺ, nous considérons sa valeur et nous pensons que les éducateurs pourraient accepter cette vérité ou même quʹils devraient lʹaccepter. Mots clés: philosophie de lʹIslam, la connaissance du curriculum, la formation du savoir, lʹéducation et les politiques, le multiculturalisme